Konsep Mutu, Mutu Sekolah, Mutu Lembaga Pendidikan Sekolah - Makmur Syukri; Muhammad Ridho Alfattah (Departement of Mathematics Education, 2024)
Quality is the main need of every person, every institution and even every country, so the slogan Quality is everybody's business emerged, where efforts to obtain and improve quality are everyone's main agenda. Quality is a challenge for business and educational institutions because they are faced with the problem of how to manage quality in the face of global competition. A school that is